2020
DOI: 10.17159/wsa/2020.v46.i1.7889
|View full text |Cite
|
Sign up to set email alerts
|

The potential use of plant species within a Renosterveld landscape for the phytoremediation of glyphosate and fertiliser

Abstract: In South Africa, fertiliser and herbicide pollutants resulting from agricultural practices indirectly lead to the degradation of surface freshwater and groundwater quality. Nitrogen and phosphorus, and glyphosate, derived from agricultural fertiliser and herbicide applications, respectively, contribute to watercourse toxicity. Adjacent to many of the surface freshwater systems are some of South Africa’s most productive agricultural lands, where natural ecosystems are converted to croplands, resulting in the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Despite the general and widespread use of glyphosate, its phytoremediation has been poorly investigated. Jacklin et al (2020) evaluated the effects of glyphosate in 14 plant species in constructed wetlands. The planted wetlands removed an average of 96.8% of the 0.7 mg L –1 glyphosate while the unvegetated wetlands (control) removed 92.2%, suggesting the relevance of the glyphosate adsorption to the soil and the need to ensure the local biodegradation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the general and widespread use of glyphosate, its phytoremediation has been poorly investigated. Jacklin et al (2020) evaluated the effects of glyphosate in 14 plant species in constructed wetlands. The planted wetlands removed an average of 96.8% of the 0.7 mg L –1 glyphosate while the unvegetated wetlands (control) removed 92.2%, suggesting the relevance of the glyphosate adsorption to the soil and the need to ensure the local biodegradation.…”
Section: Discussionmentioning
confidence: 99%
“… Source: Mench et al 50 , 55 Khalid et al 7 , 49 Jacklin et al 6 , 50 , 54 56 Kahangwa et al 6 , 50 , 54 56 Lee et al 6 , 50 , 54 56 and Tindwa and Singh. 39 , 52 , 57 …”
Section: Remediation Technology Of Eeccmentioning
confidence: 99%
“…heavy metals), obstruct their flow, and prevent interaction with contaminated soils 7 , 49 During the process of phytodegradation, plants take up EECCs from polluted soils, metabolize them, and convert them into volatile organic compounds, less-toxic byproducts, or less-harmful vapors using certain enzymes. 7 , 50 , 55 , 56 In general, phytoremediation trials conducted in previous studies have demonstrated efficacy in eliminating EECCs from contaminated areas. 6 , 50 , 54 56 …”
Section: Remediation Technology Of Eeccmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytoremediation of gold tailings-contaminated soils in South Africa using Vetiver grass (Chrysopogon zizanioides) has also been reported (90). Others include use of water hyacinth for bioremediation of water and sediments in the Hartbeespoort Dam, South Africa (91) and Cyperus textilis for phytoremediation of soils contaminated with glyphosate-based herbicide pollutants along the Breede River of the Western Cape Province of South Africa (92).…”
Section: Technologies That Involve Extraction Of the Contaminant From...mentioning
confidence: 99%